Diagnostic Accuracy of Umbilical Cord Bilirubin Measurement in Development of Significant Hyperbilirubinemia in Healthy Neonates - Taimur Khalil Sheikh, Rubina Zulfiqar, Tariq Mahmood (Journal of Rawalpindi Medical College, 2018)
Background: To determine the diagnostic accuracy of umbilical cord blood bilirubin in determining the development of significant hyperbilirubinemia on the 3rd day of life in healthy full term newborns, keeping serum bilirubin as a gold standard. Methods: In this cross sectional study babies delivered consecutively were taken.Any condition which can aggravate hyperbilirubinemia and any patient with congenital abnormality were excluded. Cord blood sample was collected from the neonatal end of the umbilical cord after it had been cut and investigated for serum total bilirubin (STB). Venous sample was taken on the 3rd day of life and sent for serum total bilirubin. Babies were then discharged or admitted for treatment depending on their serum total bilirubin levels. Mean serum total bilirubin in cord blood and mean total serum bilirubin on 3rd day of life was calculated. A 2 x 2 table was constructed to determine sensitivity, specificity positive and negative predictive values. Results: The mean cord STB was 2.0 mg/dl ± 0.6. Out of the 115 babies, 26% developed significant hyperbilirubinemia requiring phototherapy, only one needed exchange transfusion. The results showed that cord blood bilirubin ≥2.5mg/dl had the high sensitivity (87%) and specificity (98%) to predict the newborn that would develop significant hyperbilirubinemia. At this level the negative predictive value was 95%. The diagnostic accuracy of cord bilirubin 94.8%. Conclusion: A cord blood STB of ≥2.5md/dl is predictive of significant hyperbilirubinemia on the 3rd day of life in healthy neonates